Akuntansi Untuk Semua: Literasi Digital Sebagai Alat Inklusi Keuangan Dan Keadilan Sosial - Anggya Pratnya Paramitha; Bintang Sabrina Lumban Raja; Laudia Triska Dewi; Putri Amalia Widyaningtias (Jurnal Riset Mahasiswa Akuntansi, 2026)
In the digital era, the gap in access to simple financial record-keeping still often hinders the realization of social justice. This study aims to determine the role of digital literacy in promoting inclusion, particularly in the fields of finance and social justice for all levels of society. This research uses a quantitative method distributed through questionnaires to people who have businesses, and the data is analyzed using Microsoft Excel. This research identifies the pattern of the relationship between digital literacy skills and access to digital finance among marginalized groups. The results of this study indicate that low digital literacy, particularly in the use of financial applications, leads to weak financial record-keeping and limited use of digital wallets/banking products. Conversely, the presence of digitalization training with communities and guidance in simple accounting practices using digital financial platforms has been proven to increase economic participation and reduce disparities in financial access. Simple accounting can improve accountability and the quality of community decisions. Digital literacy accelerates the adoption of simple accounting and the expansion of access for marginalized groups. Equitable access to these three elements will realize social justice for all. The conclusion of this study is that digital literacy is not merely a skill but a strategy in realizing digital financial inclusion. This research can serve as a foundation for the government to be able to implement equitable access to digitalization that is beneficial for economic growth.